The ambiguities of rapid enlargement in regional organisations and prospects for East African regional integration - Stroh, Alexander (The Round Table : The Commonwealth Journal of International Affairs and Policy Studies, 2026)
This article explores the implications of the East African Community’s rapid enlargement from three to eight members – including conflict-affected countries. By assessing institutional and political consequences of the EAC’s widening, considering experiences from the European Union and ASEAN, the study argues that enlargement does not inherently impede deepening but requires strategic institutional adaptations. The EAC stands at the crossroads between its federalist ambitions and an even more intergovernmentalist model. The outcome will hinge on the management of security issues and the political willingness to pool sovereignty. Indecision risks leading the community into a widening gap between treaty ambitions and political reality.
Keywords: Regional integration; East Africa; enlargement; deepening; institutional reform